2016
DOI: 10.1055/s-0042-106084
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Supplementation of Microencapsulated ursodeoxycholic Acid Prevents Hypertension in a Mouse Model of Insulin Resistance

Abstract: Hypertension is a significant comorbidity associated with insulin resistance and type-2 diabetes. Limited evidence show that ursodeoxycholic acid (UDCA) has some anti-hypertensive effects. However, the potential effect of UDCA on hypertension induced by type-2 diabetic insulin resistance has not been reported. In C57Bl6 wild-type mice, insulin resistance was induced by the chronic ingestion of diet enriched in fat and fructose (HFF). HFF mice were randomized to treatment with UDCA or candersartan incorporated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 18 publications
2
20
0
4
Order By: Relevance
“…Mice were randomly allocated to either control or diabetic group ( n = 20). The sample size was determined based on previous studies (Al-Salami et al, 2017 ; Mamo et al, 2017 ). Mice in control group received standard low-fat (LF) chow (AIN-93M, Specialty Feeds, WA, Australia), while diabetic group received a pro-diabetic diet containing high fat and fructose (HFF; 30% (w/w) lard, 0.5% (w/w) cholesterol and 15% (w/w) fructose (SF14-088, see Supplementary Tables S1, S2 for detail).…”
Section: Methodsmentioning
confidence: 99%
“…Mice were randomly allocated to either control or diabetic group ( n = 20). The sample size was determined based on previous studies (Al-Salami et al, 2017 ; Mamo et al, 2017 ). Mice in control group received standard low-fat (LF) chow (AIN-93M, Specialty Feeds, WA, Australia), while diabetic group received a pro-diabetic diet containing high fat and fructose (HFF; 30% (w/w) lard, 0.5% (w/w) cholesterol and 15% (w/w) fructose (SF14-088, see Supplementary Tables S1, S2 for detail).…”
Section: Methodsmentioning
confidence: 99%
“…PB-LVSA (F1-without ULCA as control) and PB-ULCA-LVSA (F2-with ULCA as test) microcapsules were prepared using our established system (BÜCHI Labortechnik AG, Flawil, Switzerland) based on our developed technology: the ionic gelation vibrational jet flow technique [29,55]. Multiple parameters were used, including a frequency of 1800 Hz with a constant air pressure of 350 mbar, and a liquid flow rate of 5 mL/min; these parameters were constant for both microcapsules.…”
Section: Microcapsules Preparationmentioning
confidence: 99%
“…In gastrointestinal (GI) fluid, the hydrated LVSA matrix changes into the porous, insoluble acid matrix and when it reaches higher pH values (the small intestine), the alginate acid matrix is transformed into a soluble viscous layer that breaks down the polymer integrity and releases drugs from the microcapsules [53,54]. Previously, our lab has demonstrated that sodium alginate-based formulation improved pharmacokinetics and pharmacodynamics responses with optimized structural, chemical, and physical compatibility and improved targeted delivery [31,55,56]. This study is a preliminary study to elucidate the application of our ionic gelation vibrational jet flow technology in nano/microcapsule production, before moving a step further toward an in vivo animal study of anti-oxidant for T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…The bile acids CDCA, LCA and UDCA concentrations in plasma, tissues and faeces will also be measured. The study is a continuation of ongoing work in our laboratory examining the preclinical efficacy of dual ingredient antioxidant-bile acid microcapsules in diabetes mellitus with published hypoglycaemic effects of controlled groups 3,11,14,[27][28][29][30][31][32][33][34][35] .…”
mentioning
confidence: 99%